EFFECTS OF ENTREPRENEURSHIP AND BUSINESS ETHICS ON BUSINESS RESTAURANT BEHAVIOR PONTIANAK CITY - Donna Febrilia; Nuraini Asriati; Herkulana Herkulana (Universitas Tanjungpura, 2019)
AbstractThe purpose of this study is to determine the effect of Entrepreneurship and Business Ethics on Restaurant Business Conduct in Pontianak City. The research method used is a type of causality study. The population in this study were 136 restaurants spread throughout the city of Pontianak and were sampled in this study. Data analysis using SPSS version 16.00. The sample used are 97 Padang restaurants. The techniques used to collect data needed in the analysis of the discussion are: Non-participant observation techniques, questionnaires and interviews. Testing the data analysis was done using Multiple Linear Regression Analysis. Based on the results of the study, it was found that the average entrepreneurial of restaurants was in the poor category, while the average business ethics of restaurants was in the poor category while the average business behavior of restaurants was in the good category. Based on the results of the study it can be concluded that there is a significant effect of entrepreneurial knowledge. Keywords: Entrepreneurship, Business Ethics, Restaurant Business Behavior